EVALUASI KINERJAPELAYANAN KESEHATAN PADAPUSKESMAS DI KOTA SEMARANG TAHUN 2012 - Wukir Sariyanti; Purwoko .; Tri Cahyo Utomo (Journal of Politic and Government Studies, 2014)
Public services, especially health services still have a lot of obstacles and barriers mostlyon the quality of the service given. Public service organizations that have an interest in accordancewith the basic rules and procedures have been established. The paradigm emerging during the publicservices management tends to be more directive and focusing only on the interests which indicate afield fact that there is deficiency in the performance of health services in health centers (Puskesmas).Based on that fact, the need of evaluation on performance of health service in health centers is amust. Health centers as one of government agencies which play role in delivering health services tosociety must be able to meet people's satisfaction on their needs of health services.The objectives of this research are to evaluate the performance of health centers publicservices in Semarang and to find out the problems encountered also the factors supporting theirperformance there. To strengthen and achieve the objectives of this study, evaluative method isbeing used. The prosedure of data collection is by spreading questionnaire to and interviewing bothproviders and recipients of the heath services in the health centers, or in this case the visitors, healthworkers, and related agencies in Semarang Health Office. In addition, to support the completion ofthe needed information, related data and documents are also being used.The result of the research shows that from overall user satisfaction indicators of healthservices in health centers, 56.93% survey respondents stated that the services is very good, 38.57%stated that services is good, 4.63% stated that is poor and 0.14% stated that the services is not good.The result also shows that the problems encountered on the process of delivering health services inthe health centers are the lack of personnel officer and readiness, lack of facility and infrastructure,slow medical treatment, less understanding and knowledge of the visitors and lack of medicalsupplies.